Evaluation of Whitening Effects and Identification of Potentially Active Compounds Based on Untargeted Metabolomic Analysis in Different Chrysanthemum Cultivar Extracts - Fenglan Wang; Huiya Liu; Zifeng Huang; Yangyang Zhang; Yitong Lu; Yiwei Zhou (Antioxidants)
Chrysanthemum is a traditional Chinese medicinal herb. Chrysanthemum extracts are rich in bioactive compounds; however, there are few reports evaluating the whitening effects of organic chrysanthemum extracts. This study assessed the antioxidant and whitening effects of organic extracts from the petals of five chrysanthemum cultivars from Guangdong, China. Significant differences were observed among the five cultivars across various parameters, including IC50 values for tyrosinase inhibition activity, DPPH and ABTS values, UV absorption, and SPF values. Additionally, there were notable variations in total flavonoid, total phenolic, and chlorogenic acid contents. The BJ cultivar extract exhibited strong antioxidant capacity and superior whitening effects, containing the highest levels of total flavonoids, total phenolics, and chlorogenic acid. Correlation analysis indicated a significant relationship between total flavonoid content and IC50 of DPPH, and between chlorogenic acid and both IC50 of ABTS and SPF. Untargeted metabolomic analysis of three representative cultivars (BJ, WYHJ, and JSHJ) identified 22 compounds potentially related to antioxidant and whitening effects. Compounds significantly correlated with multiple antioxidant or whitening indicators (p < 0.05, r > 0.8) included tangeritin, hydroquinone, eupatilin, quercetin 3-(6″-malonyl-glucoside), biochanin A, and cyanidin 3-glucoside. These compounds may play crucial roles in the antioxidant and whitening effects of chrysanthemum extracts. The results highlight the promising antioxidant and whitening properties of chrysanthemum extracts, with certain genotypes, such as BJ, showing potential as superior raw material sources.